2010 Annual International Conference of the IEEE Engineering in Medicine and Biology 2010
DOI: 10.1109/iembs.2010.5627886
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of “biomechatronic gym” for early detection of neurological disorders in infants

Abstract: The study and measurement of grasping actions and forces in humans is important in a variety of contexts. In infants, it can give insights on the typical and atypical motor development, while it poses functional and operative requirements that are not fully matched by current sensing technology. Novel approaches for measuring infants' grasping actions are based on sensorized platform usable in natural settings. A new set of instrumented toys has been designed for the assessment/stimulation of upper limbs of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…As newborn infants are inherently uncooperative subjects, a further requirement of the device is that their natural movements can be safely measured under natural conditions [ 6 , 19 ]. To allow for handling by a newborn infant, the proposed tool should be small and lightweight, and its shape should be appropriate to improve engagement and encourage palmar grasping [ 26 ].…”
Section: Basic Requirements and Components Of The Smart Graspable mentioning
confidence: 99%
See 1 more Smart Citation
“…As newborn infants are inherently uncooperative subjects, a further requirement of the device is that their natural movements can be safely measured under natural conditions [ 6 , 19 ]. To allow for handling by a newborn infant, the proposed tool should be small and lightweight, and its shape should be appropriate to improve engagement and encourage palmar grasping [ 26 ].…”
Section: Basic Requirements and Components Of The Smart Graspable mentioning
confidence: 99%
“…The majority of these studies have utilized technologies to assess grasping behavior in terms of strength and holding time, as well as to investigate the relationship between grasping pattern and intrinsic (e.g., infant gender, weight, premature births) and extrinsic factors (e.g., object shape and texture) [ 14 , 15 ]. The aforementioned measuring systems have used pressure transducers based on electrical components which are unusable inside the MRI scanner [ 6 , 16 , 17 , 18 , 19 ]. MR-compatible technology requires unconventional solutions to ensure safety due to the strong static magnetic field and avoid electromagnetic interference (EMI), with further attention required for successfully imaging infant subjects.…”
Section: Introductionmentioning
confidence: 99%
“…An instrumented sorting block toy was shown to be sufficiently sensitive to demonstrate differences in performance related to motor planning and task difficulty ( 31 ). This concept has also been extended further for babies by integrating intelligent toys into a baby gym, providing an engaging and involving enriched environment for an ecological assessment of reaching patterns and grasping forces in infants aged between 4 and 9 months ( 32 , 34 , 35 ). Longitudinal trials have demonstrated that this system is capable of providing quantitative measures of power grip maturation patterns in healthy infant subjects, and has the potential to be employed to objectively assess hand function in this naturally uncooperative population ( 34 , 36 ).…”
Section: Early Infant Motor Development and Assessmentmentioning
confidence: 99%
“…This concept has also been extended further for babies by integrating intelligent toys into a baby gym, providing an engaging and involving enriched environment for an ecological assessment of reaching patterns and grasping forces in infants aged between 4 and 9 months ( 32 , 34 , 35 ). Longitudinal trials have demonstrated that this system is capable of providing quantitative measures of power grip maturation patterns in healthy infant subjects, and has the potential to be employed to objectively assess hand function in this naturally uncooperative population ( 34 , 36 ). Meaningful measures about standing balance and gait in older children have also been derived from commercial gaming devices such as the Nintendo Wii, with the advantage that the device is generally familiar and attractive to the children being assessed ( 37 ).…”
Section: Early Infant Motor Development and Assessmentmentioning
confidence: 99%
“…It is a technological and modular system able to provide, by means of tele-rehabilitation, a home and personalized intervention for very young infants (for further details see [15, 16]). CT allows subjects to carry out an early, intensive, individual EI carried out at home by parents consisting of highly customized exercises (rehabilitative packages called scenarios) remotely monitored by a clinical staff [1518].…”
Section: Introductionmentioning
confidence: 99%